A genre-based exploration of intertextuality and interdiscursivity in advertorial discourse. (April 2021) - Deng, Liming; Laghari, Tania; Gao, Xiaoping
Abstract: Nowadays, it is very difficult to find pure genres in the real world of discourse. Professional writers often appropriate and exploit generic resources to invade other genres in discourse construction in order to achieve social and private intentions. One of the most dominant genres that have invaded other genres is the promotional genre. However, little research has investigated this genre from an intertextual and interdiscursive perspective. This study critically analyzed 80 advertorials from different magazines by examining the use of intertextuality and interdiscursivity references. The results indicate that direct reporting strategies of intertextuality are heavily employed in advertorials. The study also shows that the utilization of intertextual references exhibits some specific interconnection between a particular text and a genre. Meanwhile, through interdiscursive analysis, it demonstrates the ways in which generic resources of one particular genre are skillfully appropriated to create another promotional genre by the specific discourse community. Findings as such have both pedagogical implications and practical insights for ESP practitioners, learners as well as professional writers in various contexts. Highlights: The study analyses the discursive practices of advertorials from intertextual and interdiscursive perspectives. Direct reporting strategies of intertextuality are found to be extensively employed in advertorial discourse. Genre mixing is evidently employed in advertorial discourse to highlight the effect of persuasion of advertorial. The study reveals that advertising and editorial genres are being colonized to form an impressive hybrid genre. The findings shed light on the nature of intertextual and interdiscursive practices in the particular professional context.